Module development strategy of active learning collaborative online course platform openlearning TITAS MOOC in the Malaysian public universities - Mohd Yusoff, Ahmad Nasir; Ab Razak, Nurmahfuzah (UTM Academic Leadership (UTMLead), Universiti Teknologi Malaysia, 2016)
Teaching modules become an important guide to the lecturer at the millennium to 21. The development of teaching technology and web 1.0 applications and the latest web 2.0 requires mastery of the lecturers especially with the birth of Gen 'Y', Gen 'Z' and now Gen 'Z Alpha'. interest and attraction of learning should be adapted to the climate of this technology. The process of teaching and learning must be a transformation and strategy. Active learning is online for collaboration with the 'tools' must stimulate enthusiasm and motivation in the process of P & P. For TITAS based courses MOOC (Massive Open Online Course) should be in line with the 'tools' to boost the process of P & P.